MODERN METHODS AND TECHNOLOGIES OF LEARNING ENGLISH IN THE EXAMPLE OF CULTURE AND LANGUAGE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This thesis explores the integration of cultural elements into English language learning through innovative interactive methods and technologies. It argues that cultural immersion, project-based learning, multimedia resources, role-playing activities, gamification, workshops, and community engagement significantly enhance linguistic proficiency and cultural understanding among learners.